Musthofa Sha'ban's Perspective on Arabic Listening Assessment for Beginners - Lalu Rahmat Sugiara; R. Ummi Baroroh; Amy Fitriani Siregar; Khaerul Muttakin; Ilham Dhya'ul Wahid (Journal of Arabic Language Teaching, 2025)
The listening comprehension test (maharah istima') instrument for basic-level Arabic learners is still limited and has not yet been able to measure language competence comprehensively. Previous studies have emphasized literal understanding but have paid less attention to phonetic, cognitive, and visual dimensions, resulting in suboptimal instruments. This study aims to analyze and formulate the standardization of the maharah istima' test based on Musthofa Sya'ban's perspective, which is relevant to the needs of beginners. The method used is a library research approach, with primary data from Ma'ayir Lughawiyah and secondary data from books, journals, and scientific articles. The analysis was conducted through identifying key concepts, categorizing themes, and comparing them with previous research findings to develop a conceptual model. This study offers a listening comprehension test model based on Musthofa Sya'ban's standards suitable for beginners. It thus can serve as a reference in developing Arabic language evaluation instruments at the basic level. Instrumen tes pemahaman menyimak (maharah istima') bagi pembelajar bahasa Arab tingkat dasar masih terbatas dan belum mampu mengukur kompetensi berbahasa secara komprehensif. Penelitian-penelitian sebelumnya lebih menekankan pada pemahaman literal, namun kurang memperhatikan dimensi fonetik, kognitif, dan visual, sehingga menghasilkan instrumen yang kurang optimal. Penelitian ini bertujuan untuk menganalisis dan merumuskan standarisasi tes maharah istima' berdasarkan perspektif Musthofa Sya’ban yang relevan dengan kebutuhan pemula. Metode yang digunakan adalah pendekatan penelitian kepustakaan, dengan data primer yang bersumber dari Ma’ayir Lughawiyah dan data sekunder dari buku, jurnal, serta artikel ilmiah. Analisis dilakukan melalui identifikasi konsep-konsep kunci, pengelompokan tema, serta perbandingan dengan temuan penelitian terdahulu untuk mengembangkan model konseptual. Penelitian ini menawarkan model tes pemahaman menyimak berdasarkan standar Musthofa Sya’ban yang sesuai untuk pembelajar tingkat dasar. Dengan demikian, hasil penelitian ini dapat menjadi rujukan dalam pengembangan instrumen evaluasi pembelajaran bahasa Arab pada tingkat dasar.